Numerical modeling and analysis of the dynamic motion response of an offshore wind turbine blade during installation by a jack-up crane vessel. (1st October 2018) - Zhao, Yuna; Cheng, Zhengshun; Sandvik, Peter Christian; Gao, Zhen; Moan, Torgeir; Van Buren, Eric
Abstract: Jack-up crane vessels are commonly used to install offshore wind turbine blades and other components. A jack-up crane vessel is subjected to wind and wave loads, which cause motion at crane tip. Excessive motion at crane tip can lead to failure of lifting operations. Therefore, the crane tip motion should be properly assessed for jack-up crane vessels. In this study, a fully coupled model is developed for a typical elevated jack-up crane vessel, considering the hydrodynamic and aerodynamic loads on the vessel, the soil-structure interaction, and the structural flexibility of the jack-up legs and crane. The vessel model developed is further coupled with the SIMO-Aero code to achieve a fully coupled aero-hydro-soil-elastic-mechanical code SIMO-RIFLEX-Aero for numerical modeling and dynamic analysis of offshore single blade installation using jack-up crane vessels. The SIMO-RIFLEX-Aero code is then applied to study the dynamic response of the DTU 10 MW wind turbine blade installed by a typical jack-up crane vessel under various wind and wave conditions. The results show that significant motion is induced at crane tip, mainly due to wave loads. It is important to consider the structural flexibility of the jack-up legs and crane when modeling the installation of offshore wind turbine blades. Highlights: An integrated aero-hydro-soil-elastic-mechanical simulation tool is developed for simulating offshore single blade installed by a jack-up crane vessel. The numerical model of the elevated vessel is evaluated by comparison against standard recommendations. The simulation tool is applied to simulate the installation of the DTU 10 MW wind turbine blade. It is important to consider the flexibility of the jack-up legs and crane when modeling offshore single blade installation. The methodology developed can be applied to deal with other types of lifting operations using jack-up crane vessels.